Requirements Engineering: Foundation for Software Quality 16th International Working Conference, REFSQ 2010, Essen, Germany, June 30-July 2, 2010. Proceedings - Wieringa, Roel.; Persson, Anne.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This volume compiles the papers accepted for presentation at the 16thWorking C- ference on Requirements Engineering: Foundation for Software Quality (REFSQ 2010), held in Essen during June 30 and July 1-2, 2010. Since 1994, when the first REFSQ took place, requirements engineering (RE) has never ceased to be a dominant factor influencing the quality of software, systems and services. Initially started as a workshop, the REFSQ working conference series has now established itself as one of the leading international forums to discuss RE in its (many) relations to quality. It seeks reports of novel ideas and techniques that enhance the quality of RE products and processes, as well as reflections on current research and industrial RE practices. One of the most appreciated characteristics of REFSQ is that of being a highly interactive and structured event. REFSQ 2010 was no exception to this tradition. In all, we received a healthy 57 submissions. After all submissions had been ca- fully assessed by three independent reviewers and went through electronic disc- sions, the Program Committee met and finally selected 15 top-quality full papers (13 research papers and 2 experience reports) and 7 short papers, resulting in an acc- tance rate of 38 %. The work presented at REFSQ 2009 continues to have a strong anchoring in pr- tice with empirical investigations spanning over a wide range of application domains.
Keynote -- Keynote Talk Piecing Together the Requirements Jigsaw-Puzzle -- Decision-Making in Requirements Engineering -- Understanding the Scope of Uncertainty in Dynamically Adaptive Systems -- Use of Personal Values in Requirements Engineering – A Research Preview -- Requirements and Systems Architecture Interaction in a Prototypical Project: Emerging Results -- Scenarios and Elicitation -- Videos vs. Use Cases: Can Videos Capture More Requirements under Time Pressure? -- Supporting the Consistent Specification of Scenarios across Multiple Abstraction Levels -- Product Families I -- Requirements Value Chains: Stakeholder Management and Requirements Engineering in Software Ecosystems -- Binary Priority List for Prioritizing Software Requirements -- Requirements Patterns -- Towards a Framework for Specifying Software Robustness Requirements Based on Patterns -- A Metamodel for Software Requirement Patterns -- Validation of the Effectiveness of an Optimized EPMcreate as an Aid for Creative Requirements Elicitation -- Product Families II -- Towards Multi-view Feature-Based Configuration -- Evaluation of a Method for Proactively Managing the Evolving Scope of a Software Product Line -- Requirements Engineering in Practice -- Challenges in Aligning Requirements Engineering and Verification in a Large-Scale Industrial Context -- On the Perception of Software Quality Requirements during the Project Lifecycle -- Lessons Learned from Integrating Specification Templates, Collaborative Workshops, and Peer Reviews -- A Case Study on Tool-Supported Multi-level Requirements Management in Complex Product Families -- Natural Language -- A Domain Ontology Building Process for Guiding Requirements Elicitation -- Tackling Semi-automatic Trace Recovery for Large Specifications -- Ambiguity Detection: Towards a Tool Explaining Ambiguity Sources -- Ambiguity in Natural Language Software Requirements: A Case Study -- Security Requirements -- On the Role of Ambiguity in RE -- Towards a Framework to Elicit and Manage Security and Privacy Requirements from Laws and Regulations -- Visualizing Cyber Attacks with Misuse Case Maps -- Poster -- How Do Software Architects Consider Non-Functional Requirements: A Survey.
Keywords: Software engineering; Computer communication systems; Application software; Management information systems; Computer science; Computers and civilization; Software Engineering/Programming and Operating Systems; Software Engineering; Computer Communication Networks; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Computers and Society